2014
DOI: 10.1002/vnl.21358
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of accelerators on curing characteristics, tensile, and dynamic mechanical properties of (natural rubber)/(recycled ethylene‐propylene‐diene‐monomer) blends

Abstract: The migration of sulfur from natural rubber (NR) compound to the ground waste ethylene‐propylene‐diene monomer (EPDM) rubber phase may have caused the cure incompatibility between these two rubbers. Optimization of accelerators had been adopted to overcome the cure incompatibility in NR/(R‐EPDM) blends as well as to get increased curative distribution. In this study, blends of NR and R‐EPDM were prepared. The effect of accelerator type on curing characteristics, tensile properties, and dynamic mechanical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…7. The increasing of ΔM is connected with increasing of cross-link density, which was also observed by other authors [26]. The higher values of cross-link density was generally observed for the vulcanizates obtained using naphthenic oil in comparison to vulcanizates obtained using polyurethane glycolysate contained the same amount of plasticizer, but increasing amount of plasticizer in the case of materials contained polyurethane glycolysate resulted in lower decreasing of cross-link density and difference between maximum and minimum torsion moment.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…7. The increasing of ΔM is connected with increasing of cross-link density, which was also observed by other authors [26]. The higher values of cross-link density was generally observed for the vulcanizates obtained using naphthenic oil in comparison to vulcanizates obtained using polyurethane glycolysate contained the same amount of plasticizer, but increasing amount of plasticizer in the case of materials contained polyurethane glycolysate resulted in lower decreasing of cross-link density and difference between maximum and minimum torsion moment.…”
Section: Resultssupporting
confidence: 83%
“…It was also observed that maximal torque (MH) values decreasing with increasing amount of plasticizer and higher values of mentioned parameter was observed for the NR mixes prepared using naphthenic oil. The maximal torque is related to the stiffness and shear modulus of vulcanized compounds [25][26][27]. The higher stiffness of natural rubber/carbon black composites prepared using naphthenic oil is resulted from the decreasing mobility of polymer chains, which is in good correlation with the results from the static tensile test (higher tensile strength and lower elongation at break) in comparison to the composites obtained using polyurethane glycolysate as a plasticizer.…”
Section: Resultsmentioning
confidence: 59%
“…The type of used accelerator and the ratio of accelerator to sulfur had no real effect on the changes of (Table 5). Similar observations were recently presented in research work published by Ismail et al [11] where application of conventional curing system (accelerator/sulfur ratio was 1:2) increased the values of ΔM that was corresponded with the cross-link density of vulcanizates [7]. In the case of incorporation of MBT and DPG accelerators into effective curing systems (EV) significant decrease of ΔM (cross-link density) value was observed.…”
Section: Curing Characteristicssupporting
confidence: 88%
“…[28,29] On the other hand, crosslinking of rubber compounds with using of TMTD accelerator promotes formation of polysulfide crosslinks, which can evolve into disulfide and monosulfide crosslinks. During this transformation, accelerator dissolved in SBR/GTR blends may improve compatibility of the blends, [30] which is confirmed by the values of estimated mechanical properties (see Table 1). For better presentation of the differences during vulcanization process, curing curves for SBR/mGTR are shown in the Figure 2.…”
Section: Gtr Modificationsupporting
confidence: 53%